Apparent prevalence and risk factors associated with occurrence of Coxiella burnetii infection in goats and humans in Chhattisgarh and Odisha, India. (October 2018) - Sahu, Radhakrishna; Kale, Satyajit B.; Vergis, Jess; Dhaka, Pankaj; Kumar, Manesh; Choudhary, Mamta; Jain, Lata; Choudhary, Binod Kumar; Rawool, Deepak B.; Chaudhari, Sandeep P.; Kurkure, Nitin V.; Malik, S.V.S.; et al.
Highlights: High positivity was observed against Coxiella burnetii among goats and humans using ELISA. None of the environmental and rodent samples were positive for C. burnetii using PCR. Temporary housing was found to be a significant risk factor for occurrence of C. burnetii in the herd. Abstract: Coxiella burnetii is one of the most contagious pathogen associated with Q fever in humans, while, ruminants act as important source of infection for humans. In the present cross sectional study, a total of 464 samples were collected from 218 goats comprising of 218 sera, 218 blood and 28 milk from various parts of Chhattisgarh and Odisha region, India. Besides, environmental (33; soil- 4, faecal- 10, feed-6, drainage water- 6, drinking water- 7) and rodent (38) samples were also collected from the premises of the animals. Human sera samples (93) were collected from same sampling area comprised of workers at an organized dairy farm (43), and farmers (50). The samples were subjected to PCR targeting the trans and com1 genes and detection of antibodies using commercial ELISA kits. An overall 14.22% (95% CI: 10.2–19.47%) of the goat samples were positive using either PCR or ELISA. While, by using PCR and ELISA, 11.93% (26/218) and 9.63% (21/218) of the samples were positive for C. burnetii. A higher seropositivity (46.24%; 95% CI: 36.46–56.32%) was observed for antibodies against C. burnetii in samples collected from humans. None of the human, environmental and rodent samples were positive for C. burnetii using PCR. This seems to be the first cross sectional study to focus the hidden threat of coxiellosis among goat population and associated risk factors in India.